Impacts Of Nonlinear Stimulated Raman Scattering On The Performance Of Optical Codedivision Multiple-Access Transmission Systems - Taqi Al-Qazwini, Zaineb A. (2008)

(untitled)
Code-division multiple access (CDMA) is a well-known scheme for multiplexing communication channels that is based on the method of directsequence spread spectrum. This concept was introduced into fiber optic communication systems in the middle of 1980’s as optical CDMA (OCDMA), where encoding and decoding operations are all performed in optical domain using optical devices and large number of users with asynchronous access capability. In addition to the good performance at high number of users and asynchronous access to the network, OCDMA systems provide the users with high security by coding the data before transmission and at the same time using this code to recover the data at the receiver. However, there are various nonlinear effects that limit the performance of OCDMA systems. In particular, nonlinear stimulated Raman scattering (SRS) causes the optical power from one mode to be transferred in the forward direction to the same, or other modes, at a different frequency. The process of SRS can severely limit the performance of multi-channel communication systems through the transfer of energy between the signals at different wavelengths. The main motivation behind this research is the need to understand signal distortion due to SRS in OCDMA transmission systems. Specially, there is no real attention paid to investigate this issue in OCDMA systems while most of researches that study nonlinear effects are based on wavelength-division multiplexing (WDM) systems. Therefore, this work is attempting to understand SRS effects on the performance of OCDMA systems as a function of system design parameters (i.e. power per chip, transmission distance, and number of users), and hence, to determine the fundamental transmission limits in OCDMA systems in the presence of SRS nonlinear effects. The system performance is evaluated by measuring the bit-error-rate (BER) and tilt ratio which indicates the power transfer between the chips at different wavelength. It is demonstrated through numerical simulations that the performance of OCDMA systems, at high input powers, large number of users and/or long transmission distances, is significantly degraded due to SRS effects. Furthermore, the transmission limits to keep the performance of the system under study within acceptable levels in the presence of SRS effects is estimated according to the BER threshold of 10-9 and 10-12.